Waste Reduction Analysis with Lean Manufacturing Approach - Eulis Yulianti Faridah; Trio Yonathan Teja Kusuma (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2023)
UPT Logam Yogyakarta is one of the manufacturing industries engaged in metal casting services. UPT Logam Yogyakarta has the status of a Regional Business Service Agency so that this company has the capacity to receive requests from local and foreign consumers. One of the requests produced is the product Panasonic Downlight NN511. The problem that occurs in this company is the waste that occurs in the production process which results in losses to the company because the production output is not optimal. This can be indicated from the capacity of the production machine in the form of a sophisticated automated die casting machine with the ability to produce a Panasonic Downlight NN511 product per 45 seconds that cannot be utilized optimally, due to an unbalanced production path caused by waste and non-value added time. As a result, the production capacity of 1040 pcs per day cannot be achieved, and is only able to produce at the rate of 200-300 pcs. As a calculation reference to determine the degree of accuracy, a adequacy and uniformity test of the data will be carried out, then calculate the rating factor and determine the allowance for the calculation of normal time and standard time. After testing and adjusting the data with the factor rating and allowance, it was found that there was a cycle time that was greater than the taktime, it explained that the metal UPT had to reduce the cycle time at the finishing and packaging stations to be able to meet customer demands. One of the large proportions of waste is the waiting time in the production process. The analysis to determine the root cause of the problem is carried out using a fishbone diagram. To optimize available resources and increase production efficiency, several continuous improvements are needed in the flow pattern of the Panasonic Downlight NN511 production process. balancing, compiling the layout using Activity Relationships Chart, and collapsing diagrams. From these improvements, it is hoped that Yogyakarta Metals UPT in producing the Panasonic Downlight NN511 can achieve a higher level of productivity.